Community Health Profile of Four VDCs of North-West Part of Kathmandu - Shrestha, Lochana; Pant, Shambhu Nath; Rajbhandari, Sanjeev Das; Malla, Sudha Sen; Zoowa, Sabin Bahadur (Medical Journal of Shree Birendra Hospital, 2013)
Introduction: There are different hidden health related problems in community. These needs to be identify and adhered by effective, efficient tools to bring the better outcomes. One of the effective tools for the identification and quantification of the health problems in a community is Community Health Diagnosis. The aim of this study was to find out the common health problems in community, describe the related demographic, education, socio –economic and environmental factors and to convey health message to improve health profile of community. Methods: Four weeks Community Health Diagnosis was conducted in four selected VDCs after feasibility studies in 16 VDCs. Sample size households (HH) were calculated based on morbidity status of each VDCs. Students covered allocated number of Households in each VDCs by selecting household with convenience sampling method. Results: In all studied VDCs, nuclear family was the commonest, CBR and literacy rate were good compared to national figure. Population pyramid showed that active age group was more in these VDCs. There was lack of government tap for drinking water and latrine. Maternal parameters were found to be better than national fi gure. Conclusions: Though there is more illiteracy rate in all studied VDCs compare to national figure, maternal parameters, child health indicators and fertility rates are better which may be the impact of effective health education.  Medical Journal of Shree Birendra Hospital; January-June 2013/vol.12/Issue1/32-36DOI: http://dx.doi.org/10.3126/mjsbh.v12i1.9090